Formate concentrations in maternal plasma during pregnancy and in cord blood in a cohort of pregnant Canadian women: relations to genetic polymorphisms and plasma metabolites. Issue 5 (27th July 2019) - Brosnan, John T; Plumptre, Lesley; Brosnan, Margaret E; Pongnopparat, Theerawat; Masih, Shannon P; Visentin, Carly E; Berger, Howard; Lamers, Yvonne; Caudill, Marie A; Malysheva, Olga V; O'Connor, Deborah L; Kim, Young-In
ABSTRACT: Background: One-carbon metabolism, responsible for purine and thymidylate synthesis and transmethylation reactions, plays a critical role in embryonic and fetal development. Formate is a key player in one-carbon metabolism. In contrast to other one-carbon metabolites, it is not linked to tetrahydrofolate, is present in plasma at appreciable concentrations, and may therefore be distributed to different tissues. Objective: The study was designed to determine the concentration of formate in cord blood in comparison with maternal blood taken earlier in pregnancy and at delivery and to relate formate concentrations to potential precursors and key fetal genotypes. Methods: Formate and amino acids were measured in plasma during early pregnancy (12–16 wk), at delivery (37–42 wk), and in cord blood samples from 215 mothers, of a prospective cohort study. Three fetal genetic variants in one-carbon metabolism were assessed for their association with cord plasma concentrations of formate. Results: The formate concentration was ∼60% higher in the cord blood samples than in mothers' plasma. The maternal formate concentrations did not differ between the early pregnancy samples and those taken at delivery. Plasma concentrations of 4 formate precursors (serine, glycine, tryptophan, and methionine) were increased in cord blood compared with the maternal samples. Cord blood formate was influenced by fetal genotype, being ∼12% higher in infants harboring the MTHFR A1298C (rs1801131) AC or CC genotypes and 10% lower in infants harboring the MTHFD1 G1958A (rs2236225) GA or AA genotypes. Conclusions: The increased formate concentrations in cord blood may support the increased activity of one-carbon metabolism in infants. As such, it would support increased rates of purine and thymidylate synthesis and the provision of methionine for methylation reactions.